Education and the Knowledge Society Information Technology supporting human development - Weert, Tom J. van.; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
Engineering the Knowledge Society (EKS) - Event of the World Summit on the Information Society (WSIS) This book is the result of a joint event of the World Federation of Engineering Organisations (WFEO) and the International Federation for Information Processing (IFIP) held during the World Summit on the Information Society (WSIS) in Geneva, Switzerland, December 11 - 12, 2003. The organisation was in the hands of Mr. Raymond Morel of the Swiss Academy of Engineering Sciences (SATW). Information Technology (or Information and Communication Technology) cannot be seen as a separate entity. Its application should support human development and this application has to be engineered. Education plays a central role in the engineering of Information and Communication Technology (ICT) for human support. The conference addressed the following aspects: Lifelong Learning and education,- inclusion, ethics and social impact, engineering profession, developing- society, economy and e-Society. The contributions in this World Summit event reflected an active stance towards human development supported by ICT. A Round Table session provided concrete proposals for action.
A comprehensive synthesis of research -- A comprehensive synthesis of research -- Lifelong Learning in the Knowledge Society -- Lifelong Learning in the Knowledge Society -- Collective intelligence and capacity building -- Collective intelligence and capacity building -- ETampere -- ETampere -- Information: a strategic resource for technological change -- Information: a strategic resource for technological change -- Preserving information -- Preserving information -- Towards an Indigenous vision for the Information Society -- Towards an Indigenous vision for the Information Society -- Vulnerabilities of information technologies -- Vulnerabilities of information technologies -- Professional deontology, self-regulation and ethics in the Information Society -- Professional deontology, self-regulation and ethics in the Information Society -- Developments in the fields of Software Engineering -- Developments in the fields of Software Engineering -- The role of IEEE computer society in the Information Age -- The role of IEEE computer society in the Information Age -- Managing ICT skills profiles -- Managing ICT skills profiles -- Enabling ICT adoption in developing Knowledge Societies -- Enabling ICT adoption in developing Knowledge Societies -- Sustainable development and the Information Society -- Sustainable development and the Information Society -- The (3z(Be-well(3y (B-- The (3z(Be-well(3y (B-- Networked economy -- Networked economy -- Understanding and interpreting the drivers of the Knowledge Economy -- Understanding and interpreting the drivers of the Knowledge Economy -- Beyond technology -- Beyond technology -- Social engineering of the Internet in developing areas -- Social engineering of the Internet in developing areas -- Project Proposals -- The (3z(Bfour pillars(3y (Band e-education for all -- E-solidarity, a means of fighting against FGM (Female Genital Mutilation) -- An indigenous approach to bridging the digital divide -- E-well: Multi-sectoral development of rural areas -- Cybertroc: A barter system for the Information Society -- Cyber inclusion through activity -- Exploring dilemmas: Ethics, social values and e-Society -- Network-blended education of tomorrow -- ICTs for education and development in rural communities -- Just in Time Support for Educational Leadership -- Declarations -- Unesco $1 (BIFIP Youth declaration -- Vilnius declaration -- Carthage declaration -- Vienna Declaration.s
Keywords: Physics; Computers; Education -- Data processing; Computers and civilization; Educational technology; Science -- Social aspects; Physics; Societal Aspects of Physics; Theory of Computation; Computing Milieux; Computers and Society; Computers and Education; Educational Technology; Electronic books